Vehicle Operational Cost Analysis (BOK) of Mini Bus Light Vehicle Public Transportation: Case Study of Siwa-Palopo Route - Thoengsal, James; Tumpu, Miswar (Kirana Publisher (KNPub), 2025)
Land transportation, especially public transportation between cities, is very important in carrying out oneof its main functions, namely as a means of transporting people to carry out their daily activities wherethe services provided are expected to be carried out quickly, safely, comfortably, cheaply and efficiently.The puIDRose of this study was to determine the value of vehicle operating costs (BOK) for the Siwa-Palopo route using data collection methods by means of surveys and direct interviews with publictransportation operators. Based on the analysis of research data from the results of the IntercityTransportation Within the Province (AKDP) route Siwa - Palopo, the following conclusions were drawn;Mini Bus Vehicle Operating Costs with a BOK value of IDR 158,730,866, - / Year or IDR 2,701.71, - / Km.The income of Mini Bus Vehicle Owners is IDR 207,360,000 / Year or IDR 3,529.41 / Km. From the resultsof the analysis of the data calculations above, it can be seen that public transportation owners get a netprofit of IDR. 48,629,134.1,-/year or IDR. 827.70,-/km. Where the income obtained by the transportationowner is greater than the Vehicle Operating Cost.